Pengaruh Promosi, Pelayanan, Dan Trust Terhadap Keputusan Pengambilan Kredit Usaha Rakyat (KUR) Super Mikro PT BRI Unit Polehan (Studi Kasus Pada UMKM Wilayah Polehan) - Andy Prasetya Budy Nugroho; Nurhidayah Nurhidayah; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study was conducted to determine the effect of promotion, service, and trust on the decision to take Super Micro People's Business Credit (KUR) at PT BRI Unit Polehan (Case Study on MSMEs in the Polehan Region). This research belongs to the type of explanatory research with a quantitative approach, which was conducted to examine the effect between variables. The population in this study are all MSMEs that have used or are currently using Super Micro KUR in the Polehan Village area. The sampling technique used in this study used a purposive sampling technique. The criteria for sampling are MSMEs that have or are currently taking Super Micro KUR. Samples were taken using the Malhotra formula so that a sample of 75 samples was obtained. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the t test there is a partial influence between the variables of promotion, service, and trust on the decision variables of credit makers. Adjusted R Square of 48.2% to the dependent variable, namely the decision to take credit can be explained by the variables of promotion (X1), service (X2), trust (X3) while 51.8% is explained by other variables outside the research model. Keywords: Credit Decision Making, Promotion, Service, Trust